Freehand correction of scoliosis in Rett’s syndrome - Mehdian, Hossein (Springer-Verlag, 2013)
We present the case of an 18-year-old girl with a scoliosis (long C-shaped curve) in association with an atypical Rett’s syndrome. In order to attain a full correction and to provide her with adequate posture and sitting balance, segmental instrumentation was utilised from the high thoracic spine to the pelvis. We describe the procedure including the relevant pre-operative, intra-operative and post-operative imaging. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00586-013-2685-9) contains supplementary material, which is available to authorized users.